Assessment of Social Dimensions (ASD) in Environmental Impact Studies in the State of Kuwait - Alajmi, Manahi; Abdu, Anwar; Bashir, Badraldeen; Mohamed, Abdelhadi; Alsarawi, Mohammed (Jordan Journal of Social Sciences, 2021)
This study aims to provide synthesis of the social (dimensions) impacts in EIA studies of four development projects, analyze their outputs and compare them with the social impact assessment criteria of the World Bank, UNEP and JICA. And to demonstrate the significance of applying these criteria in environmental impact assessment studies. The descriptive and documentary approach was used to assess and analyze data pertaining to social dimensions in the environmental impact assessment studies. Then the contents of the social dimensions were compared with the criteria of the international institutions with the aim of identifying the extent of social impacts coverage in the environmental impact assessment studies. The results show the absence of ASD in an integrated detail which indicate that most of the projects has been implemented considering environmental impacts only, which in turn makes it difficult to develop policies, plans and programs for environmental management and mitigation of the negative impacts of development projects. Comparison of six (6) World Bank criteria with the assessment of social dimensions in EIA studies for four projects indicates that the health impacts of these projects have been evaluated in all the projects. The impacts of projects on environmental resources and community participation have been assessed in two studies, while the method of predicting and evaluating the resulting impacts have been analyzed in three projects. The project’s impact on affected groups and resource utilization patterns were not assessed in all the EIA studies. Comparison of four (4) UNEP criteria with the assessment of social dimensions in EIA studies of four projects, indicates that, projects impacts on population change has been assessed in three studies. While project impacts on future generations and cultural values of local communities have been completely ignored .The impacts of the projects on community services and the need to address and mitigate their negative impacts have been assessed in all the studies. A comparison of four (4) JICA criteria with the EIA studies has shown that consequences of direct effects of social and environmental impacts and the analysis of their social and environmental cost benefits have been evaluated in three studies. While the existence of alternatives and precautionary measures to reduce the negative impacts of projects have been assessed in two projects. Assessment of the dissemination and disclosure of information to all stakeholders has been neglected in all studies. The study recommendations include: to consider and legislate ASD as an integral part of the EIA studies, or as a parallel process, or a separate study. To link the social dimensions issues with other development and environmental planning will provide a framework for the management of social change and achieving sustainable development.